REVIEW OF WIRELESS MIMO CHANNEL MODELS (Nigerian Journal of Technology, 2016)
The need to increase spectral efficiency has led to the design of multiple antenna systems for both transmit and receive sides otherwise known as MIMO. Channel modeling forms an integral part of this design. Therefore it is very important to investigate and understand existing MIMO channel models. This paper provides a detailed review of existing MIMO channel models, their characteristics, tradeoffs and challenges. As with most models in the scientific and technical fields, open issues in MIMO channel modeling have also been enumerated. http://dx.doi.org/10.4314/njt.v35i2.20